The Severity of Malarial-Anemia in Pregnant Women in Biyem-Assi, Yaounde - Judith Lum Ndamukong-Nyanga; Ngo Batandi Helen Virginie; Tchanga Chanceline Flore; Fegue Celestine Nadege (Archives of Current Research International, 2021)
Malaria is a parasitic disease endemic in Sub-Saharan Africa especially in Cameroon. Pregnancy is associated with increased susceptibility to malaria. Closely associated to malaria is anaemia. It is generally accepted that pregnancy ends with childbirth. The outcome of the pregnancy is highly affected by the presence of malaria and anaemia. The aim of ths study was to determine the prevalence and severity of malaria and anemia among pregnant women and the influence of socio-demographic factors on malaria and anaemia prevalences in pregnant women in Biyam- Assi Yaounde. Information on socio-demographic factors was collected from 302 pregnant women attending prenatal clinics in health institutions within the Biyem-Assi Health District of Yaounde VI subdivision using a pretested questionnaire. Peripheral blood was collected and thick smears were prepared for screening Plasmodium parasites. The level of hemoglobin was measured using a haemoglobinometer URIT- 12. Analysis was done using SPSS version 20.0. Out of the 302 women, 146 (51.7%) had Plasmodium falciparum infected red cells. Among the 146 infected women, 36% had mild parasitaemia, 45% had moderate parasitaemia and 19% had severe parasitaemia. The prevalence of anemia in the study population was 53%. There was no significant association between the severity of malaria and the severity of anaemia (p > 0, 05). Parity had a significant influence on the severity of malaria. The level of school education significantly (p < 0, 05) influenced the severity of anaemia. Multiparous women were more affected by malaria than primiparous women. However, in relation to disease severity, primiparous women parasitized by Plasmodium presented a significantly higher risk of severe malaria compared to multiparous women. Malaria and anaemia prevalences in the study population were high (>50%), anaemia severity was directly associated to level of education. We recommend that more sensitization of women should be done to reduce ignorance, prevent malaria and in turn reduce anaemia and improve on the health of mother and baby.